Application of Dynamic Temperature-Humidity Chamber for Measuring Moisture Sorption Isotherms of Biomaterials as Compared to the Conventional Isopiestic Method - Maha Al-Khalili; Nasser Al-Habsi; Mohammad Shafiur Rahman (Adsorption Science & Technology, 2021)
Measurement of water activity and moisture sorption isotherms of foods and biomaterials are important to determine the state of water. In this work, a dynamic temperature-humidity (DTH) controlled chamber was used to measure water sorption isotherm and compared with the conventional isopiestic method. Temperature and relative humidity of DTH chamber can be controlled in the range of -15 to 100°C and 0 to 98%, respectively; thus, measurement of water activity at any point can be measured within the above ranges. The DTH chamber method showed high reproducibility as compared with the conventional isopiestic method when measured isotherms of cellulose, lignin, and hemicellulase were compared at 30°C. Finally, isotherm data of cellulose, lignin, and hemicellulase were generated in the temperature range of 10-90°C using DTH chamber, and these were modelled by BET and GAB equations. The model parameters were correlated with the temperature.